Children's Recall Accuracy for Repeated Events over Multiple Interviews: Comparing Information Types. Issue 6 (1st November 2016) - Hubbard, Kyle; Saykaly, Christine; Lee, Kang; Lindsay, R. C. L.; Bala, Nicholas; Talwar, Victoria
Abstract : The present study examined children's recall accuracy for a repeated event over multiple interviews. Participants took part in three play sessions and were then questioned in three separate interviews a week later. The sample included 87 children between 4 to 10 years of age. Repeated measures ANOVAs were conducted to examine total accuracy and accuracy for action (i.e., what happened during the play session) and detail (i.e., descriptions of objects, people, time, and locations) information. Older children were more accurate in their recall than were younger children, but total accuracy did not differ across interviews. Conversely, children were more accurate when recalling detail information compared to action information, and accuracy for detail information improved across the interviews, while accuracy for action information deteriorated from Interview 1 to 3. Implications for judging the accuracy of children's witness testimony in real-world forensic contexts involving multiple events and interviews are discussed.